ISENTROPIC EFFICIENCY OF GAS TURBINE AXIAL COMPRESSORS AND THE OUTDOOR TEMPERATURE EFFECT - Gašparinčić, Josip; Štricelj, Aleš (Journal of Energy Technology, 2024)
This paper presents the calculation of the isentropic efficiency of a gas turbine axial compressor manufactured by Alstom. Isentropic efficiency shows how much energy is transformed in exergy and how much into anergy. This paper presents the calculation of axial compressor characteristics of an Alstom GT11N2 thermal power plant in Brestanica, Slovenia. The efficiency changes dependant on external temperatures during 2009 are also presented.
Keywords: Gas turbine; axial turbo compressor; isentropic efficiency; temperature; pressure